2007
DOI: 10.1038/sj.onc.1210751
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of CXCL12 increases the metastatic potential of mammary carcinoma cells

Abstract: Expression of the chemokine receptor CXCR4 has been linked with increased metastasis and decreased clinical prognosis in breast cancer. The current paradigm dictates that CXCR4 fosters carcinoma cell metastasis along a chemotactic gradient to organs expressing the ligand CXCL12. The present study asked if alterations in autocrine CXCR4 signaling via dysregulation of CXCL12 in mammary carcinoma cells modulated their metastatic potential. While CXCR4 was consistently detected, expression of CXCL12 characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
112
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 33 publications
16
112
0
1
Order By: Relevance
“…2,29 Further, differences in mutational status contributing to increased resistance to CXCL12-induced anoikis is evidenced by our work showing CXCL12 re-expression in Ras mutated mammary carcinoma cells does not affect anoikis, but instead increases cellular proliferation. 18 Together with previous reports our data support the notion that the Ras, Raf, MEK, ERK pathway is a key regulator of intestinal epithelial and colorectal carcinoma cell anoikis.…”
Section: Discussionsupporting
confidence: 90%
“…2,29 Further, differences in mutational status contributing to increased resistance to CXCL12-induced anoikis is evidenced by our work showing CXCL12 re-expression in Ras mutated mammary carcinoma cells does not affect anoikis, but instead increases cellular proliferation. 18 Together with previous reports our data support the notion that the Ras, Raf, MEK, ERK pathway is a key regulator of intestinal epithelial and colorectal carcinoma cell anoikis.…”
Section: Discussionsupporting
confidence: 90%
“…In cancers, however, it has been shown that DNA hypermethylation of the CXCL12 promoter in colon carcinomas, mammary carcinomas and the MCF7 breast cancer cell line promotes tumor metastasis. [37][38][39] In the current study basal levels of CXCL12 were higher in RASFs compared with OASFs. Even though these changes were not dramatic, we believe that they are of clinical significance as CXCL12 expression positively correlated with levels of C-reactive protein.…”
Section: Dna Methylation Regulates the Expression Of Cxcl12 E Karouzasupporting
confidence: 48%
“…Our refined model for chemokine-directed metastasis includes epigenetic silencing of the ligand that confers a leukocyte migratory phenotype to carcinoma cells that is diminished by reexpression of the suppressed chemokine (13)(14)(15)25). The purpose of our study was to test whether exogenous CXCL12 treatment would also reduce metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that changes in the oligomeric state of CXCL12 dictated the migratory outcome of monocytic cells in vitro, with monomer, but not dimer, inducing cellular migration (17). Congruently, restoration of CXCL12 expression in colonic and mammary carcinoma cells markedly reduced their metastatic potential in vivo (14,15), in part, through increased sensitivity to detachment-induced cell death (15,19). We therefore speculate that local CXCL12 secretion acts as a tumor suppressor, preventing metastasis by shielding the primary tumor from remote chemotactic gradients.…”
mentioning
confidence: 99%
See 1 more Smart Citation